A covalent organic framework as a nanocarrier for synergistic phototherapy and immunotherapy. Issue 25 (27th May 2020) - Zhou, Ying; Liu, Sainan; Hu, Chunling; Cai, Lihan; Pang, Maolin
Abstract : As traditional cancer treatment methods, photodynamic therapy (PDT) and photothermal therapy (PTT) can eliminate primary tumors, but they cannot inhibit extensive tumor metastasis and local recurrence. Abstract : As traditional cancer treatment methods, photodynamic therapy (PDT) and photothermal therapy (PTT) can eliminate primary tumors, but they cannot inhibit extensive tumor metastasis and local recurrence. Herein, in order to prevent intermolecular accumulation and improve photostability, indocyanine green (ICG) is spontaneously adsorbed onto a covalent organic framework (COF) with high affinity through π–π conjugation, and then chicken ovalbumin (OVA) is coated on the surface of COF@ICG via an electrostatic interaction force. The resultant COF@ICG@OVA can ablate primary tumors under 650 nm and 808 nm laser irradiation due to its high photothermal conversion efficiency ( η = 35.75%) and ability to produce reactive oxygen species (ROS). Tumor-associated antigens are also produced after combinational PTT/PDT therapy. By further combining with anti-PD-L1 checkpoint blockade therapy, it can effectively eliminate primary tumors and inhibit the metastasis of cancer cells by generating strong immune responses. Taken together, COF@ICG@OVA nanoparticles offer an efficient synergistic therapeutic modality for the treatment of tumor metastasis.